A Meta‐Analytic Structural Model of Dispositonal Affectivity and Emotional Labor. Issue 1 (19th November 2012) - Kammeyer‐Mueller, John D.; Rubenstein, Alex L.; Long, David M.; Odio, Michael A.; Buckman, Brooke R.; Zhang, Yiwen; Halvorsen‐Ganepola, Marie D. K.
<x xml:space="preserve">Abstract</x> The exponential growth of the service economy has increased the attention that organizational researchers have paid to the concept of emotional labor. Although much progress has been made in the field, few studies have provided an integrated picture of how individual dispositions, perceived display rules, and emotional labor behaviors shape employee outcomes. To clarify and compare results across this growing body of literature, a quantitative review was developed, along with a theoretically derived path diagram of key emotional labor constructs. Evidence from our structural meta‐analytic model based on 116 primary studies demonstrates that examining affective dispositions and emotional labor constructs and the pattern of positive and negative results helps to clarify and add specificity to the literature. Results were consistent with the perspective that surface acting emotion regulation strategies have a pattern of negative relationships with work outcomes of job satisfaction and stress/exhaustion (but not with job performance), whereas deep acting emotion regulation strategies have a pattern of positive relationships with all of these work outcomes.